Perimyocarditis as First Manifestation of Systemic Lupus Erythematosus Successfully Treated with Heart Failure and Immunosuppressive Therapy - Marina Ikić Matijašević; Petra Grubić Rotkvić; Zrinka Planinić; Lucija Ikić; Ines Zadro Kordić; Edvard Galić (Journal of Cardiovascular Development and Disease, 2023)
Systemic lupus erythematosus (SLE) myocarditis is presumed to be rare, but associated with adverse outcomes. If SLE diagnosis has not previously been established, its clinical presentation is often unspecific and difficult to recognize. Furthermore, there is a lack of data in the scientific literature regarding myocarditis and its treatment in systemic immune-mediated diseases, leading to its late recognition and undertreatment. We present the case of a young woman whose first lupus manifestations included acute perimyocarditis, among other symptoms and signs that provided clues to the diagnosis of SLE. Transthoracic and speckle tracking echocardiography were helpful in detecting early abnormalities in the myocardial wall thickness and contractility while waiting for cardiac magnetic resonance. Since the patient presented with acute decompensated heart failure (HF), HF treatment was promptly started in parallel with immunosuppressive therapy, with a good response. In the treatment of myocarditis with heart failure, we were guided by the clinical signs, echocardiographic findings, biomarkers of myocardial stress, necrosis, and systemic inflammation, as well as markers of SLE disease activity.